Interview protocol about the use of open government data - Kawashita, Ilka (2022)
Dados disponíveis em: "Kawashita, Ilka; Baptista, Ana Alice; Soares, Delfina Sá, 2022, "Use of Open Government Data in the Brazilian States and Federal District Public Administrations", https://doi.org/10.34622/datarepositorium/UY7MFA, Repositório de Dados da Universidade do Minho, V1, UNF:6:ujkRdSuOtuJcHOpoSBUrPg== [fileUNF]"